THE GROWTH FACTORS OF RELIGIOUS-POLITICAL RADICALISM - Grigory Vladimirovich Volgushev (Современная наука и инновации, 2022)
In the article on the basis of factor analysis identified the key moments of the formation of violence of a religious-political roots. Much attention is paid to policy intervention on the part of States - leaders of globalization. Updated outreach attitude of Western countries to democracy «Western style».